MECHANICAL PROPERTIES OF CELLULOSE-BASED EXTRACTED FROM NATA DE COCO - Pertiwi, Sherlyna; Tarigan, Malemta; Harahap, Mahyuni; Adiansyah (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2023)
Paper production is currently important for various community needs due to the use in daily life. The aim of this study is to produce paper cellulose-based extracted from Nata de Coco with the addition of polyvinyl alcohol (PVA) as an adhesive. The paper was produced by using pulp method followed by ultrasonication with variation of ultrasonication from 10 min, 20 min, to 30 min. The sample was characterized in terms of functional groups and mechanical properties. The results showed that the longer the ultrasonication time, the lower the mechanical value. The highest tensile test was obtained at 10 min of ultrasonication with the value of 5.036 MPa.